Wittgenstein - Fogelin, Robert J. (Arguments of the philosophers., 1987)
Professor Fogelin has provided an authoritative critical evaluation of both the Tractatus Logico-Philosophicus and Philosophical Investigations, making these key texts accessible to the general reader.